Ultrasound Precautions during COVID-19 Pandemic - Delores Jones (Archives of Nursing Practice and Care - Peertechz Publications, 2022)
An epidemic that travels throughout the world is called a pandemic [1]. There have been several pandemics that have impacted the world. One example of a pandemic that became global is Spanish influenza. This pandemic was very severe and attacked more than 30% of the world population. Approximately 50 million people died from the first outbreak.